2015
DOI: 10.2146/ajhp140722
|View full text |Cite
|
Sign up to set email alerts
|

Impact of an innovative blood factor stewardship program on drug expense and patient care

Abstract: Implementation of the UNCMC stewardship program has led to improved outcomes in patients receiving clotting factor concentrates, with significant institutional cost savings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 16 publications
0
31
0
Order By: Relevance
“…A retrospective cohort evaluated the impact of a pharmacist‐led blood factor stewardship program and found that total CA during 1 year was $375,539, amounting to $8941.40 per patient . A similar study found that a pharmacist working with a hematologist resulted in an annual savings of more than $4 million in blood factor stewardship . The actual cost savings for specific types of interventions were not provided.…”
Section: Results Of Scoping Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…A retrospective cohort evaluated the impact of a pharmacist‐led blood factor stewardship program and found that total CA during 1 year was $375,539, amounting to $8941.40 per patient . A similar study found that a pharmacist working with a hematologist resulted in an annual savings of more than $4 million in blood factor stewardship . The actual cost savings for specific types of interventions were not provided.…”
Section: Results Of Scoping Reviewmentioning
confidence: 99%
“…69 A similar study found that a pharmacist working with a hematologist resulted in an annual savings of more than $4 million in blood factor stewardship. 70 The actual cost savings for specific types of interventions were not provided. An additional gap in the literature is quantification of savings from blood factors not provided, a significant means of CA within this area.…”
Section: Blood Factor Stewardship and Emergency Anticoagulation Revermentioning
confidence: 99%
“…Nevertheless, utilization patterns and outcomes may vary over time in ways that often cannot be predicted or explained, making cost predictability and budget forecasting difficult. Large prospective cohort studies can help to increase transparency and enable benchmarking between centers and regions [70][71][72][73].…”
Section: Innovative Outcome-based Care and Procurement Modelmentioning
confidence: 99%
“…The collection of real-world outcomes and utilization data from individual patients and their HCPs would facilitate cost predictability. Accurate cumulative data on populations would also provide payers with deeper insight into resource usage, real-world effectiveness, and best practice patterns across healthcare providers, hemophilia centers, regions, patient characteristics, etc [71].…”
Section: Innovative Outcome-based Care and Procurement Modelmentioning
confidence: 99%
“…Prior to the creation of the HMP, the Department of Pharmacy acted in strictly a drug acquisition and dispensing role and there existed no role for the pharmacist as part of the comprehensive care team for the hemophilia population at our medical center. Amerine et al previously described the creation of an inpatient Factor Stewardship Program, which served as a guide for the formation of the HMP at our institution . Their report demonstrated the fiscal benefit of greater pharmacist involvement in the management of factor drug formulary and clinical application to reduce expenditures and the potential for similar programs in other health systems.…”
Section: Introductionmentioning
confidence: 96%